Smartphone-based application for preventing medication errors among pediatric nurses - Kumar Jaiswal, Vinay; Srinivasa Rao, Varri (Journal of Neonatal Surgery, 2025)
Medication Errors (MEs) harm patient safety incidents across all age demographics. Medical emergencies are incredibly perilous in the juvenile demographic, especially for individuals necessitating specialized care due to the elevated frequency and severity of illness. This research sought to assess the impact of a smartphone messaging application on medical students' education concerning the avoidance of MEs in kids. This quasi-experimental research was conducted with 85 nursing pupils arbitrarily assigned to intervention and control categories. Data was obtained via a researcher-developed checklist. The research engaged with learning via Telegram, a smartphone messaging service, for three weeks. Information was examined using SPSS, employing descriptive and inferential statistics, with P < 0.04 deemed significant. The average age of the pupils was 25.4 ± 3.1 years. The predominant MEs associated with medicine events in the control categories encompassed inadequate management of the following MEs: management of high-risk medications, identification of medication incompatibilities, utilization of prescribing cards, estimation of medication dosages, understanding of adverse drug reactions, acknowledgment of pharmaceutical names during drug choice, compliance with clean and sterile techniques, practices for flushing microbore intravenous tubing, modification of intravenous drip rates, and adhering to medication management. The median scores of pupils regarding knowledge of avoiding MEs were markedly different among the two groups. Using the Telegram messaging software for smartphone learning enhances nursing students' understanding of preventing MEs in children's hospitals. The research advocates for implementing this learning method in nursing colleges to mitigate the MEs associated with drug placing an order, dosage, and delivery.